Case commentary: Bass v. Barksdale: implications for public health and home care nurses - Killion, Susan Westrick (Public Health Nursing, 1993)
A recent malpractice case involved public health nurses. Given the legal issues based on this case, recommendations can be made to help ensure legal accountability, improve practice, and minimize liability risk. Areas of concern include doctor's orders and communication relating to telephone orders, the nurse's accountability to the client, documentation and patient teaching, the physician's duty to supervise the nurse, and corporate negligence. The court's analysis of the facts in finding areas of liability can guide nurses in avoiding malpractice litigation.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/039-112-513-700-590 tex.type: [object Object]
Keywords: Community Health Nursing; Ethambutol; Female; Human; Liability; Legal; Malpractice; Nursing Records; Patient Education; Public Health Nursing; Tennessee; United States; Vision Disorders; article; dept.nur; ethambutol; female; human; iatrogenic disease; legal aspect; legal liability; malpractice; medical record; nurse; patient education; public health service; visual disorder

Enhancing evidence bases for interventions in a baccalaureate program. - Aronson, Barbara S; Rebeschi, Lisa M; Killion, Susan Westrick (Nursing education perspectives, 2007)
Modifying the sequence, objectives, and research-based content for a nursing interventions course in a baccalaureate curriculum resulted in improved outcomes including enhancement of the evidence bases for nursing interventions. A mixed methods research study demonstrated better student preparation for clinical experiences and improved satisfaction with course content, consistency, and sequencing. Faculty reported improved integration of theory, research, and practice. Although grades were slightly lower in the new course, the positive outcomes greatly outweighed this expected finding. A foundation for improving the evidence bases for future nursing practice is guided by the curricular modifications described in this article.
Place: United States Aronson, Barbara S. Department of Nursing, Southern Connecticut State University, New Haven, USA. aronsonb1@southernct.edu
Keywords: *Attitude of Health Personnel; *Curriculum; *Education; Nursing; Baccalaureate/og [Organization & Administration]; *Evidence-Based Medicine/ed [Education]; *Nursing Research/ed [Education]; *Students; Nursing/px [Psychology]; Attitude of Health Personnel; Clinical Competence; Connecticut; Curricular and course development; Curriculum; Curriculum/st [Standards]; Diffusion of Innovation; Education; Nursing; Baccalaureate; Evidence-Based Medicine; Evidence-based interventions; Faculty; Nursing; Focus Groups; Health Knowledge; Attitudes; Practice; Health Services Needs and Demand; Humans; Nursing Education Research; Nursing Methodology Research; Nursing Research; Organizational Objectives; Program Evaluation; Qualitative Research; Questionnaires; Skills laboratory; Student learning outcomes; Students; Nursing; Surveys and Questionnaires; United States; article; attitude to health; clinical competence; curriculum; dept.nur; education; evaluation; evidence based medicine; health care quality; health personnel attitude; health service; human; information processing; mass communication; nursing education; nursing methodology research; nursing research; nursing student; organization; organization and management; peer-reviewed; psychological aspect; qualitative research; questionnaire; standard; ⛔ No DOI found